Factors determining the painfulness of electroneuromyography - Ališauskaitė , U.; Garšvienė , D.; Švilpauskė-Laurynienė, J.; Ališauskienė , M. (Neurologijos seminarai, 2020)
Introduction. Electroneuromyography (ENMG) is a useful diagnostic test for the evaluation of neuromuscular disorders. The procedure is considered unpleasant or even painful due to the use of electrical stimuli and needle electrodes. In this study, we investigated the influence of demographic factors on the perception of pain during ENMG examination as well as the connection between the perception of pain and the extent of the examination, the presence of chronic pain, its characteristics, and levels of anxiety and depression in patients.Methods. 400 patients who were referred to ENMG examination participated in a questionnaire survey after the procedure. The questionnaire included rating of pain intensity experienced during ENMG procedure using numerical rating scale (NRS), basic demographic information, information about the extent of the examination, questions about previously experienced pain, and the Hospital Anxiety and Depression Scale (HADS).Results. The mean of NRS score was 3.76±2.6. There was a negative correlation between pain intensity during ENMG and education level (r=-0.12, p=0.03). There was a significant (p=0.011) correlation between the intensity of pain and the extent of ENMG examination. The procedure was more painful for the patients who experienced continuous pain before the procedure (p=0.002), and the intensity correlated with qualitative aspects of pain. There was a significant correlation between pain intensity during the examination and the emotional state of the patient (p
Keywords: pain; electroneuromyography; chronic pain